The Effect of Self-Awareness and Self-Management of Kindergarten Teachers on the Readiness to Implement the Merdeka Curriculum - Faradilla, Chita; Syamsudin, Amir (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
This research highlights the urgency of enhancing Kindergarten teachers' readiness in facing educational transformation through the Merdeka Curriculum. The study focuses on analysing the effect of: (1) teachers' self-awareness, (2) teachers' self-management, and (3) the simultaneous influence of both variables on readiness to implement the curriculum. Employing a quantitative ex post facto approach, the research involved 205 Kindergarten teachers across 17 sub-districts in Sleman Regency, Yogyakarta. Sampling was determined based on the Krejcie & Morgan Table using probability and cluster random techniques. Data were collected through questionnaires and analysed with multiple linear regression. The results indicate that self-awareness and self-management, both individually and jointly, significantly influence teachers' readiness for curriculum implementation. These findings confirm that the development of personal capacities is a crucial foundation for effective educational change. The contribution of this study lies in providing empirical evidence that strengthening self-awareness and self-management is not only beneficial for individual teacher growth but also serves as a strategic key in supporting the broader success of early childhood learning transformation under the Merdeka Curriculum.